2020
DOI: 10.1182/blood-2020-134940
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Serious Vaso-Occlusive Pain Crises and Reduction in Patient-Reported Pain Intensity: Results from the Ongoing Phase 1/2 HGB-206 Group C Study of LentiGlobin for Sickle Cell Disease (bb1111) Gene Therapy

Abstract: Background Sickle cell disease (SCD) is caused by abnormal sickle hemoglobin (HbS) and results in chronic hemolytic anemia, painful vaso-occlusive events (VOEs), and progressive vasculopathy that lead to significant morbidity. While acute vaso-occlusive pain is a defining clinical feature, chronic daily pain also contributes significantly to poor quality of life in many adult patients. The ongoing Phase 1/2 HGB-206 Study (NCT02140554) evaluating safety and efficacy of LentiGlobin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…The BB305 vector contains an additional feature, a codon replacement that causes a tryptophan to glutamine substitution at position 87 in the β-globin protein sequence (T87Q) that interferes with polymerization of HbS tetramers, thus increasing its potential efficacy in the treatment of SCD. A pilot trial using this vector to treat SCD patients provided encouraging results [ 11 ], though a larger trial (NCT0214055) showed variable response and an even stronger requirement for high VCN compared to β-thalassemia [ 79 ].…”
Section: Designing a Transgene Expression Cassettementioning
confidence: 99%
“…The BB305 vector contains an additional feature, a codon replacement that causes a tryptophan to glutamine substitution at position 87 in the β-globin protein sequence (T87Q) that interferes with polymerization of HbS tetramers, thus increasing its potential efficacy in the treatment of SCD. A pilot trial using this vector to treat SCD patients provided encouraging results [ 11 ], though a larger trial (NCT0214055) showed variable response and an even stronger requirement for high VCN compared to β-thalassemia [ 79 ].…”
Section: Designing a Transgene Expression Cassettementioning
confidence: 99%
“…The impact of gene therapy on patient QoL remains to be fully determined and should be further evaluated in future clinical trials of beti-cel. However, data from the phase 3 Hgb-207 (Northstar-2) and Hgb-212 (Northstar-3) studies showed that patients under 18 years of age who achieved transfusion independence had an improved EuroQoL 5 dimensions (Youth) (EQ-5D-Y) score (67 [range 50-96] versus 92.5 [85][86][87][88][89][90][91][92][93][94][95]) after 12 months [67,90]. In addition, HSCT has been shown to have a positive impact on both physical and emotional aspects of HRQoL in patients with TD β-thalassemia and, given GVHD was the most common cause of impaired HRQoL in these patients, a similar or greater benefit would be expected from gene therapy [67].…”
Section: Beti-cel Gene Therapy: Benefits and Challengesmentioning
confidence: 99%
“…Haematopoietic stem cell transplantation and gene therapy studies have reported patient Hb levels >100 g/l, with varying percentages of HbS 29–34 . Most patients in HSCT and gene therapy studies had their Hb increase beyond 100 g/l within six to 12 months after transplant.…”
Section: Sickle Cell Disease Therapies and Haemoglobin Elevationmentioning
confidence: 99%
“…Most patients in HSCT and gene therapy studies had their Hb increase beyond 100 g/l within six to 12 months after transplant. Patients also experienced reduction or an absence of VOCs or ACS following transplant in studies that evaluated SCD‐related clinical outcomes 32,34 . Most patients who were receiving chronic transfusion therapy before treatment were able to stop or reduce the frequency of their RBC transfusions within two to three months after gene therapy 31,32,34 .…”
Section: Sickle Cell Disease Therapies and Haemoglobin Elevationmentioning
confidence: 99%
See 1 more Smart Citation